2021
DOI: 10.5219/1639
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of gelatin from skin and bone of snakehead (Channa striata) extracted with different temperature and time

Abstract: This study aimed to determine the physicochemical properties of the skin and bone of snakehead fish as a potential source of gelatin through extraction at different temperatures and times compared to commercial gelatin. Extraction of skin and bones of wild snakehead fish (Channa striata) at different temperatures (50, 60, 70 ºC) and time (12,18, 24 hours). The pre-treatment process used a 0.1 M Ca (OH) 2 (1:6 w/v) immersion solution for 1 h and continued with 0.05 M citric acid (1:6 b/v) for 5 h. Before pre-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 59 publications
0
4
0
1
Order By: Relevance
“…Beef cheek meat and back fat were obtained from the Tamangapa Slaughterhouse, Makassar, South Sula-wesi, Indonesia. Snakehead fish gelatin used was the result of a partial hydrolysis process from a previous study [16] through pretreatment with calcium hydroxide, treatment process with citric acid, and extraction at 60 °C for 12 hours. Snakehead fish gelatin sausage formula ingredients include soy protein isolate (Marksoy 90, Shandong Crown Soya Protein Co. Ltd., China), tapioca flour (Rose Brand), milk flour (PT.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Beef cheek meat and back fat were obtained from the Tamangapa Slaughterhouse, Makassar, South Sula-wesi, Indonesia. Snakehead fish gelatin used was the result of a partial hydrolysis process from a previous study [16] through pretreatment with calcium hydroxide, treatment process with citric acid, and extraction at 60 °C for 12 hours. Snakehead fish gelatin sausage formula ingredients include soy protein isolate (Marksoy 90, Shandong Crown Soya Protein Co. Ltd., China), tapioca flour (Rose Brand), milk flour (PT.…”
Section: Methodsmentioning
confidence: 99%
“…This study will try to observe the effect of adding snakehead fish gelatin to sausage-based beef cheek meat. Rosmawati et al [16] revealed that the snakehead fish's skin had a gel strength ranging from 108:00 ± 21:40 to 278:37 ± 22:28 and its internal gel strength ranged from 41:37 ± 7:42 to 239:53 ± 20:69, treated as the foundation for the use of snakehead fish gelatin as additives that function as binders and emulsifiers at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…Adanya limbah tersebut dapat menimbulkan masalah bagi lingkungan sekitar dikarenakan pemanfaatanya yang belum maksimal (Yuliani et al, 2018). Agustin (2013) menyatakan tingginya jumlah limbah tulang ikan gabus berpotensi sebagai sumber kolagen sebagai bahan baku gelatin (Rosmawati et al, 2021).…”
Section: Pendahuluanunclassified
“…The gel strengths of gelatin extracted from scale and mixture of snakehead skin and scale at different extraction conditions are shown in Table 2. The increase in gel strength of gelatin extracted from snakehead fish by-products was observed at the extraction temperature range of 70 to 80 °C and a decrease in the gel strength of gelatin was observed at temperature higher than 90 °C and time longer than 2 h. The time extension combined with temperature rise would cause protein degradation, which could be largely detrimental to the gel network formation of gelatin (Kittiphattanabawon et al, 2010;Rosmawati et al, 2021). The gel strength of gelatin reached its highest value at 248 g and 245 g when the same extraction at 80 °C for 1 h was observed in the snakehead scale and skin and scale mixture, respectively.…”
Section: Gel Strength Of Gelatinmentioning
confidence: 99%
“…Indeed, the social demand for gelatin has increased over the last few decades because of its unique surface-active properties, allowing its wide application in the food, pharmaceutical, cosmetic, and other industries (Zhou & Regenstein, 2007). For these reasons, gelatin production from processing fish by-products has been a concern of broad interest to related-scientist groups, such as the skin of tra catfish (Thuy et al, 2022); wami tilapia skin (Alfaro et al, 2013); seabass skin (Tekle et al, 2022); and snakehead skin and bone (Rosmawati et al, 2021). However, there is no public consideration for gelatin extracted from snakehead fish by-products.…”
Section: Introductionmentioning
confidence: 99%